Islamic monetary & economic system as a solution to global economic crisis (Kuresel ekonomik krize bir cozum olarak Islami para ve ekonomik sistem), 01-02 November 2010, Kuala Lumpur / Malaysia (Conference reports) - Kayadibi, Saim (Bilsam Yayıncılık, 2011)
The 1st World Conference on Riba, jointly organized by the Thinkers Trends Resources (TTR) and Kulliyyah of Economics & Management Sciences International Islamic University Malaysia (IIUM), was held on 01-02 November 2010 at Tun Hussein Onn Hall Putra World Trade Centre, Kuala Lump. Numerous significant scholars from different part of the world focused on the contemporary challenges and scenarios in the concept of Riba. Local and international media outlets and representatives of government and social bodies, as well as the honorary president of Perdana Leadership Foundation, Mahathir Mohamad, officers from the Department of Minister, Chief Minister for the State of Perak, the Ministry of Religious Affairs, leader of Islamic Party of Britain, a representative of Christian Council for Monetary Justice of United Kingdom, also attended.